2021
DOI: 10.1007/s12686-021-01245-0
|View full text |Cite
|
Sign up to set email alerts
|

First extraction of eDNA from tree hole water to detect tree frogs: a simple field method piloted in Madagascar

Abstract: Environmental DNA (eDNA) is becoming an increasingly used tool for monitoring cryptic species within terrestrial and aquatic systems. We present the first method for extracting water from tree holes for eDNA studies of tree-dwelling frogs, and the first use of eDNA for amphibian monitoring in Madagascar. This pilot study expands on a previously developed method and aims to provide a simple field protocol for DNA extraction from very small water samples, using a relatively inexpensive kit compared to other coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…For these reasons, the use of mouth-operated aspirators substantially increases the chance of collecting specimens. The use of environmental DNA (eDNA) can also improve the detection of phytotelm species (Barata et al 2021; Mullin et al 2022), such as bromeliad-dwelling frogs. Barata et al (2021) demonstrated that C. itambe can have a high detection rate (0.97–0.98) by extracting and amplifying eDNA from water samples of as little as 120 mL.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, the use of mouth-operated aspirators substantially increases the chance of collecting specimens. The use of environmental DNA (eDNA) can also improve the detection of phytotelm species (Barata et al 2021; Mullin et al 2022), such as bromeliad-dwelling frogs. Barata et al (2021) demonstrated that C. itambe can have a high detection rate (0.97–0.98) by extracting and amplifying eDNA from water samples of as little as 120 mL.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, by using acoustic surveys, estimates will only account for, and will therefore be limited to, the number of active males in the population, which can potentially introduce bias into inferences to the whole population, especially when the sex ratio is unknown (a 50:50 sex ratio is a naïve assumption). Alternative methods are available that could be used to improve parameter estimates, such as using automated recording devices (Measey et al, 2017) or environmental DNA (Lopes et al, 2017), which has since been trialled for A. vallani at Ambohitantely (Mullin et al, 2021b). Both of these tools eliminate the requirement for the observer to be at the site at the same time as the species, enabling data collection on much larger spatial and temporal scales and improving the robustness of any inferences made, although both tools require significant technical expertise.…”
Section: Discussionmentioning
confidence: 99%
“…The environmental DNA (eDNA) left by canopy fauna on the surfaces of leaves and bark or within canopy aquatic microhabitats may also enter stemflow. Continuing with the tree frog example, the dendrotelmata or phytotelmata in which many tree frogs rely for food, shelter and/or breeding have recently been found to house detectable levels of their eDNA (Barata et al, 2021;Mullin et al, 2022). During large storms, these canopy aquatic microhabitats overflow and drain down tree stems (as discussed in greater detail in the following sections), potentially delivering the eDNA to the surface at the base of the tree stem.…”
Section: Canopy Faunamentioning
confidence: 99%